A Survey of Regulatory Interactions Among RNA Binding Proteins and MicroRNAs in Cancer - Liu, Ying; Pan, Chu; Kong, Dehan; Luo, Jiawei; Zhang, Zhaolei (Frontiers in Genetics, 2020)
Recent advances in genomics and proteomics generated a large amount of trans regulatory data such as those mediated by RNA binding proteins (RBPs) and microRNAs. Since both types of trans regulators largely target 3’ UTR of mRNA transcripts, it is likely that there would be interactions, i.e. competitive or cooperative effect, among these trans factors. We compiled the available RBP and microRNA binding sites, mapped them to the mRNA transcripts, and correlated the binding data with mRNA expression data generated by TCGA (The Cancer Genome Atlas). We separated pairs of RBPs and microRNAs into three scenarios: those that have overlapping target sites on the same mRNA transcript (overlapping), those that have target sites on the same mRNA transcript but non-overlapping (neighboring), and those that do not target the same mRNA transcript (independent). Through a regression analysis on expression profiles, we indeed observed interaction effects between RBPs and microRNAs in the majority of the cancer expression data sets. We further discussed implication of such widespread interactions in the context of cancer and diseases.